The Effect of Planting Media and Nutrient Flow on the Growth of Hydroponic Lettuce with the NFT System - Ahyaniah Dewi Syabarina; Ramdan Hidayat; Didik Utomo Pribadi (The University of Lampung, 2026)
Lettuce is a type of vegetable plant that is consumed by the wide community. Hydroponic lettuce cultivation has become an alternative as land area decreases as a result of land-use conversion. This research aims to determine lettuce growth which is influenced by the type of planting media and nutrient discharge. This study was conducted at the Greenhouse Emak Farm and Hidroponik Wadungasri, Waru District, Sidoarjo Regency, East Java, adopting a Split Plot Design with the main plot of nutrient solution discharge (L) consisting of 3 levels, namely L1 = 1.5 L/min; L2 = 2 L/min; L3 = 2.5 L/min. The subplot is the planting media (M) consisting of 4 types, namely M₁ = rockwool; M₂ = rice husk charcoal; M₃ = cocopeat; M₄ = fern. The observed variables comprised leaf number, leaf area, plant height, stem diameter, total plant biomass, stem and leaf biomass, root biomass, harvest index, and plant age. The results indicated that the combination of fern-based growing media and a nutrient solution flow rate of 1.5 L/min produced the most favorable outcomes for all measured parameters, with the exception of the harvest index. Nutrient flow rate of 1.5 L/min was recommended for hydroponic using fern growing media.